A transitividade em notícias sobre violência doméstica na perspectiva da LSF - PINHEIRO, Bárbara Furtado (2022)
This research aimed to uncover the representations of victims, aggressors and police in news that deal with domestic violence in the State of Pará published by the newspaper Diário Online from 2012 to 2020. To this end, the realized transitivity system was described in the texts, according to the theoretical, analytical and methodological orientation of Systemic-Functional Linguistics (HALLIDAY, 2004; CUNHA; SOUZA, 2011; FUZER; CABRAL, 2014). The methodology focuses on documentary and descriptive research, and the corpus is part of the news textual genre and consists of nine texts published in the Online Journal. In this sense, 118 sentences of these texts were collected as a procedure of analysis, taking into account the context of use of these clauses. The results indicated the presence of 63.56% of material processes, which points to greater representation in the texts of tangible actions that can be visualized that affect, mostly, victims of domestic violence. In addition, 21.19% of verbal processes, 9.32% relational, 4.24% mental, and 1.69% behavioral processes were detected. No existential processes were found in the corpus. It is concluded that, through the system of transitivity, the newspaper Diário Online portrayed the main participants involved in cases of domestic violence (victim, aggressor and police) by means of particular forms of representation, such as blaming the victims for the crimes, omission of the responsibility and guilt of the aggressors, as well as euphemising violence against women.